Cobalt Based Nanoparticles Embedded Reduced Graphene Oxide Aerogel for Hydrogen Evolution Electrocatalyst. (20th May 2019) - Koo, Sung Hwan; Li, Dong Jun; Yun, Taeyeong; Choi, Dong Sung; Lee, Kyung Eun; Lee, Gil Yong; Oh, Youngtak; Lim, Joonwon; Padmajan Sasikala, Suchithra; Lee, Ho Jin; Kim, In Ho; Jung, Hong Ju; et al.
Abstract: Efficient water electrolysis catalyst is highly demanded for the production of hydrogen as a sustainable energy fuel. It is reported that cobalt derived nanoparticle (CoS2, CoP, CoS|P) decorated reduced graphene oxide (rGO) composite aerogel catalysts for highly active and reliable hydrogen evolution reaction electrocatalysts. 7 nm level cobalt derived nanoparticles are synthesized over graphene aerogel surfaces with excellent surface coverage and maximal expose of active sites. CoS|P/rGO hybrid aerogel composites show an excellent catalytic activity with overpotential of ≈169 mV at a current density of ≈10 mA cm −2 . Accordingly, efficient charge transfer is attained with Tafel slope of ≈52 mV dec −1 and a charge transfer resistance ( R ct ) of ≈12 Ω. This work suggests a viable route toward ultrasmall, uniform nanoparticles decorated graphene surfaces with well‐controlled chemical compositions, which can be generally useful for various applications commonly requiring large exposure of active surface area as well as robust interparticle charger transfer. Abstract : Fabrication of cobalt based nanoparticles embedded reduced graphene oxide (rGO) aerogel is presented . By freeze‐drying and heat treatment, CoS2, CoP, CoS|P decorated rGO could be obtained with small, uniform nanoparticle distribution. Maximal active surface of CoS|P nanoparticles on rGO leads to overpotential of 169 mV at 10 mA cm −2 at 0.5m H2 SO4 toward hydrogen evolution reaction.